Management of Clinically Involved Lateral Lymph Node Metastasis in Locally Advanced Rectal Cancer: A Radiation Dose Escalation Study - Pang, Xiaolin; Huang, Liang; Ma, Yan; Liu, Zhanzhen; Xie, Peiyi; Liu, Hailing; Wan, Xiangbo; Liu, Shuai; Zheng, Jian (Frontiers in Oncology, 2021)
Background: Patients with lateral lymph nodes (LLNs) metastasis are not effectively treated with neoadjuvant chemoradiotherapy. This study aimed to compare the efficacy of three neoadjuvant therapeutic regimens, namely, chemotherapy, chemoradiotherapy, and chemoradiotherapy, with a dose boost of LLNs, and to identify the optimal approach for treating LLNs metastasis of locally advanced rectal cancer. Methods: A total of 202 patients with baseline LLNs metastasis (short axis ≥ 5 mm) and treated with neoadjuvant treatment, followed by radical surgery from 2011 to 2019, were enrolled. The short axis of the LLNs on baseline and restaging MRI were recorded. Survival outcomes were compared. Results: In the booster subgroup, shrinkage of LLNs was significantly greater than in the neoadjuvant chemotherapy and chemoradiotherapy subgroups (P < 0.001), without increasing radiation related side effects (P = 0.121). For patients with baseline LLNs of short axis ≥ 5 mm in the booster subgroup, the response rate (short axis < 5 mm on restaging MRI) was 72.9%, significantly higher than for patients in the neoadjuvant chemotherapy subgroup (48.9%, P = 0.007) and higher than for patients in the neoadjuvant chemoradiotherapy group (65.0%), but there was no statistical difference (P = 0.411). The 3-year local recurrence and lateral local recurrence rates were both 2.3% in the dose booster group, which were lower than those of the other two subgroups (local recurrence: P < 0.001; lateral local recurrence: P < 0.001). The short axis of lateral lymph nodes (≥ 5 mm and < 5 mm) on restaging MRI was an independent risk factor for prognosis (P < 0.05). Conclusion: Radiation dose boost is an effective way of increasing the response rate and decreasing recurrence rates. The restaging LLNs with short axis ≥ 5 mm is a predictor of poor prognosis.